Intra-arterial thrombectomy in the management of acute ischemic stroke: evidentiary analysis over the past two years - Cunha, Gabriel Veloso; Fernandes, Guilherme da Silva; Azenha, Ettore Mendes; Grippe, Talyta Cortez (Clinical and Biomedical Research, 2017)
Stroke is one of the main causes of death and disability worldwide, and the ischemic modality is responsible for the majority of these events. Despite its high occurrence and potentially unfavorable prognosis, the management options were scarce and barely effective until recent times, when a relatively new endovascular intervention with demonstrated superior efficacy as compared with that of classic management was reported in the medical literature. The theoretical basis of this study was conducted through research in virtual databases Public MEDLINE (PubMed) and Scientific Electronic Library Online (SciELO) using associations among the keywords “acute ischemic stroke”, “ischemic stroke”, “thrombectomy”, “endovascular,” and “intra-arterial thrombectomy”. Clinical trials, meta-analysis, and pertinent literature reviews published in the last two years were reviewed and 14 articles were selected for complete and critical evaluations. The results of the randomized clinical trials, consequences of implantation of the intra-arterial thrombectomy as routine management for eligible groups, cost-effectiveness, and the most related complications and outcomes associated with the procedure are critically explored throughout this study. Keywords: Stroke; ischemic stroke; thrombectomy; endovascular